2019
DOI: 10.1175/jcli-d-18-0310.1
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Dynamic Responses to Deforestation in the Maritime Continent: A Modeling Study

Abstract: Tropical deforestation can result in substantial changes in local surface energy and water budgets, and thus in atmospheric stability. These effects may in turn yield changes in precipitation. The Maritime Continent (MC) has undergone severe deforestation during the past few decades but it has received less attention than the deforestation in the Amazon and Congo rain forests. In this study, numerical deforestation experiments are conducted with global (i.e., Community Earth System Model) and regional climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 78 publications
2
51
0
Order By: Relevance
“…Winckler et al (2019a) showed that the reason for this discrepancy lies in the analyses of observation-based effects of deforestation, which eliminate the non-local effects that propagate signals outside the location of deforestation by advection or changes in atmospheric circulation and constitute mostly a cooling for deforestation. Chen and Dirmeyer (2020) confirmed for temperature extremes that accounting for atmospheric feedbacks could reconcile observations and model simulations.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Winckler et al (2019a) showed that the reason for this discrepancy lies in the analyses of observation-based effects of deforestation, which eliminate the non-local effects that propagate signals outside the location of deforestation by advection or changes in atmospheric circulation and constitute mostly a cooling for deforestation. Chen and Dirmeyer (2020) confirmed for temperature extremes that accounting for atmospheric feedbacks could reconcile observations and model simulations.…”
Section: Introductionsupporting
confidence: 54%
“…Future analyses of the deforest-glob experiments could further focus on the seasonality of vegetation and climate variables (e.g. with regard to large-scale atmospheric circulation changes) to advance the understanding compared to previous studies (Bonan, 2008;Chen and Dirmeyer, 2020;Davin and de Noblet-Ducoudré, 2010;de Noblet-Ducoudré et al, 2012;Pitman et al, 2009). Additionally, the enhanced meridional temperature gradient may alter the large-scale atmospheric circulation that deserves future explorations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While deforestation usually causes less evapotranspiration and higher temperature, leading to reduced precipitation [16][17][18], precipitation in deforested areas could also be more extensive than that in high-density forests [19]. Reference [20] further indicated that deforestation could increase local convection and precipitation by introducing more lateral water vapor transport from the surrounding oceans over the Maritime Continent regions.…”
Section: Introductionmentioning
confidence: 99%